(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Transphenoidal endoscopic approach is the minimal invasive surgery in case of pituitary adenoma. Objective: To see the outcome of transphenoidal endoscopic approach in case of pituitary tumour. Results: This study was carried among the 48 patients and out of them 32 (66.7%) patients were male and 16(3.33%) were female. It was documented that in 48 patients, 44(91.66.3%) were macroadenoma and 4(8.33%) were microadenoma. Among 48 patients, 44 (91.66%) had preoperative visual disturbance and 4(8.33%) had normal vision. Tumor was totally removed in 44(91.66%) patients in endoscopic approach. Clinically 46(95.8%) patients were improved in endoscopically. One (2.1%) patient developed pneumocephalus and meningitis. In 1 (2.1%) patient, carotid artery was partially torn, which was managed by nasal pack. Conclusion: It was concluded that endoscopic endonasal approach is safe and effective procedure.